2013
DOI: 10.1159/000351136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Percutaneous Nephrolithotomy, Shock Wave Lithotripsy, and Retrograde Intrarenal Surgery for Lower Pole Renal Calculi 10-20 mm

Abstract: Objective: To compare the results of percutaneous nephrolithotomy (PCNL), shock wave lithotripsy (SWL), and retrograde intrarenal surgery (RIRS) for 1- to 2-cm lower pole kidney stones. Patients and Methods: This retrospective study was based on data collected from the files of patients between January 2007 and May 2012. The files of 383 patients (221 SWL, 144 PCNL, 38 RIRS) were evaluated. The groups were compared for stone size, success rate, and complication rate using the modified Clavien grading system. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 20 publications
1
36
0
4
Order By: Relevance
“…The SFR data in our study is very consistent with the result of previous studies by Ozturk et al [17] and Kumar et al [18]. Furthermore, we observed that the re-treatment rate for SWL was higher than that of UMP and FURS (p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The SFR data in our study is very consistent with the result of previous studies by Ozturk et al [17] and Kumar et al [18]. Furthermore, we observed that the re-treatment rate for SWL was higher than that of UMP and FURS (p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of SWL is influenced by the size of the stone, the composition of the stone, the lower calyceal angle and the patient's body habitus, which may reduce the effect of SWL and increase the rate of retreatment [4]. The other milestone as far as minimally invasive interventions for treatment of renal stones is PCNL [5]. Even though PCNL is the first-line therapy with the highest success rate, its relatively higher invasiveness and complication rates have prompted a search for alternative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for exclusion: renal stones >2 cm (n = 8), renal stones 1-3 cm (n = 1), and kidney stones 10 mm or less (n = 1). Finally, seven studies [5][6][7][8][9][10][11] were included in the meta-analysis, three RCT [5][6][7] and four CCT [8][9][10][11], published between 2012 and 2014. The literature screening process has been shown in Fig.…”
Section: Study Descriptionmentioning
confidence: 99%
“…[6][7][8] In the AUA guideline, this rate has been given as 78 percent. [4] In our study, in 74 patients, a 70.3% stone-free rate has been detected.…”
Section: Discussionmentioning
confidence: 99%